The Role of Risk Management in Reducing Organizational Collapse Analytical study at Iraqi Southern Cement Company - Ammar Abdulamir Zwen; Waleed A. J. Al-daamee; Ali H. Hindee (مجلة الغري للعلوم الاقتصادية والادارية)
The purpose of this paper is to measure the effectiveness of risk management in reducing organizational collapse, was based The current research was based on two variables interacting with each other to form the theoretical and applied framework under a laboratory hypothesis model (risk management and organizational collapse), the study has started from a problem that has been expressed with a number of questions aimed at answering them to clarify the theoretical subject and the practical goals the fact that these variables are topics of a factual nature of the phenomenon in the industrial environment of the country, hence the diagnosis of causation, the sample was made up of officials of the southern Iraqi Cement Company to diagnose the extent to which it relied on risk management and had identified That sample of (45) individual of those who are at various administrative levels. The paper used various statistical tools to analyze and manipulate data and information by adopting software-ready statistical software such as (SPSS. V.21), The fact that research is an approach to scientific research based on cognitive analysis is an analytical diagnostic research and its importance is that it will produce results and recommendations based on the reality of the application of risk management and organizational collapse and the extent to which a company is able to cope with the critical positions it is facing. The paper found that hypotheses indicate the existence of correlation and influence between their variables were validated and the research concluded that the company's interest with the reality of risk management, which gives it an ability to cope with the organizational collapse, in turn, recommendations have been made in line with the realities of the conclusions.